2016
DOI: 10.1096/fj.15-279869
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the substrate repertoire of ADAMTS2, 3, and 14 significantly broadens their functions and identifies extracellular matrix organization and TGF‐β signaling as primary targets

Abstract: A disintegrin and metalloproteinase with thrombospondin type I motif (ADAMTS)2, 3, and 14 are collectively named procollagen N-proteinases (pNPs) because of their specific ability to cleave the aminopropeptide of fibrillar procollagens. Several reports also indicate that they could be involved in other biological processes, such as blood coagulation, development, and male fertility, but the potential substrates associated with these activities remain unknown. Using the recently described N-terminal amine isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 52 publications
(77 reference statements)
4
91
0
Order By: Relevance
“…As a consequence, the destruction of the ECM induced by immune cells could trigger a process resembling wound healing (31,32), whereas ECM components could be produced by other stromal cells or tumor cells. Therefore, we found an overexpression of genes not only responsible for the degradation (32,33) but also for the production of ECM components in immune active samples, demonstrating that the remodeling of the ECM could be a dynamic process, in which different molecules and cells interact in the microenvironment in response to tumors. Besides, we also found numerous genes responsible for the remodeling of adipose tissues, which were predominantly overexpressed in most of the immune active tumor samples.…”
Section: Discussionmentioning
confidence: 82%
“…As a consequence, the destruction of the ECM induced by immune cells could trigger a process resembling wound healing (31,32), whereas ECM components could be produced by other stromal cells or tumor cells. Therefore, we found an overexpression of genes not only responsible for the degradation (32,33) but also for the production of ECM components in immune active samples, demonstrating that the remodeling of the ECM could be a dynamic process, in which different molecules and cells interact in the microenvironment in response to tumors. Besides, we also found numerous genes responsible for the remodeling of adipose tissues, which were predominantly overexpressed in most of the immune active tumor samples.…”
Section: Discussionmentioning
confidence: 82%
“…While the direct molecular mechanism by which Adamts2 expression acts to regulate these five target genes is unknown, recent work has suggested that Adamts2 may act as a upstream regulator of TGF-β signaling through direct cleavage of the proteins TGF-β RIII and DKK3 (Bekhouche et al, 2016). Dkk3 , a known cardioprotective molecule in HF also resides within module 5.…”
Section: Discussionmentioning
confidence: 99%
“…Bekhouche et al. 28 recently identified additional substrates for this group of enzymes, including several proteins involved in transforming growth factor β (TGFβ) signalling.…”
Section: Adamtssmentioning
confidence: 99%